CONTRIBUTION TO KNOWLEDGE OF THE BIOLOGY OF CORVINE PLAGIOSCION SQUAMOSISSIMUS (PERCIFORMES: SCIAENIDAE) IN UCAYALI - Riofrío Q., José C. (2009)
In the study, 321 individuals of Plagioscion squamossissimus were analyzed from July 2003 to June 2004 to obtain the length - weight relation, sex ratio, egg-laying seasonality, mature size, and composition of their diet. The length - weight relation did not show significant differences between sexes, and therefore the combined equation PT = 0.0057708 LT 3.21 is proposed for the species. The sex ratio was close to 1:1. The mature size was 29.6 cm in males and 31.2 cm in females. Variations in the gonad-somatic index (IGS) showed that this species reproduce throughout the year, but more frequently between September and October (end of dry season) and between February and March (mid and end of rainy season). The diet of the species was mainly composed by fishes.